2015
DOI: 10.1038/srep16868
|View full text |Cite
|
Sign up to set email alerts
|

Additional Arctic observations improve weather and sea-ice forecasts for the Northern Sea Route

Abstract: During ice-free periods, the Northern Sea Route (NSR) could be an attractive shipping route. The decline in Arctic sea-ice extent, however, could be associated with an increase in the frequency of the causes of severe weather phenomena, and high wind-driven waves and the advection of sea ice could make ship navigation along the NSR difficult. Accurate forecasts of weather and sea ice are desirable for safe navigation, but large uncertainties exist in current forecasts, partly owing to the sparse observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 36 publications
1
48
0
Order By: Relevance
“…Flow‐dependent errors tagged by large ensemble spreads at upper levels were expected to be advected with high‐PV air along the polar vortex because of strong westerly winds, affecting the reproducibility of the atmospheric circulation at the surface around and below this PV. During summer, the influence of Arctic radiosonde observations would be limited to high latitudes, because of the small spatial scale of the polar vortex and its decreased interaction with lower latitudes [ Inoue et al ., ]. During winter, however, when the horizontal scale of the polar vortex is greater, the additional radiosonde observations can influence much more extensive areas (to the midlatitudes), because of a stronger jet stream and its frequent meanderings.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow‐dependent errors tagged by large ensemble spreads at upper levels were expected to be advected with high‐PV air along the polar vortex because of strong westerly winds, affecting the reproducibility of the atmospheric circulation at the surface around and below this PV. During summer, the influence of Arctic radiosonde observations would be limited to high latitudes, because of the small spatial scale of the polar vortex and its decreased interaction with lower latitudes [ Inoue et al ., ]. During winter, however, when the horizontal scale of the polar vortex is greater, the additional radiosonde observations can influence much more extensive areas (to the midlatitudes), because of a stronger jet stream and its frequent meanderings.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This revealed that continental cold air outbreaks were better predicted in both events if the initial data included the additional observations. It has been assumed that the sparseness of data over the Arctic is a source of error in reanalysis data and forecasts [e.g., Inoue et al, 2013Inoue et al, , 2015, particularly in relation to upper troposphere circulations. Flow-dependent errors tagged by large ensemble spreads at upper levels were expected to be advected with high-PV air along the polar vortex because of strong westerly winds, affecting the reproducibility of the atmospheric circulation at the surface around and below this PV.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…As a related research, Inoue et al . [] revealed that additional Arctic observations were useful for predicting strong winds associated with the intense high‐pressure system and sea‐ice patterns along the NSR. As a more practical way, surface weather data sent from drifting buoys [ Inoue et al ., ] and commercial ships along the NSR would be useful for further improving the initial condition of weather and sea‐ice forecasts.…”
Section: Discussionmentioning
confidence: 99%
“…• Model realism as well as improvements to weather forecasts would benefit from additional observations 91 in the Arctic and subarctic, and by improving global and Arctic meteorological reanalyses, particularly in their representation of surface fluxes 92,93 .…”
Section: The Way Forwardmentioning
confidence: 99%